2020
DOI: 10.3350/cmh.2020.0126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of coronavirus disease 2019 in patients with pre-existing liver diseases: A multicenter study in South Korea

Abstract: Background/Aims: Although coronavirus disease 2019 (COVID-19) has spread rapidly worldwide, the implication of pre-existing liver disease on the outcome of COVID-19 remains unresolved.<br/>Methods: A total of 1,005 patients who were admitted to five tertiary hospitals in South Korea with laboratory-confirmed COVID-19 were included in this study. Clinical outcomes in COVID-19 patients with coexisting liver disease as well as the predictors of disease severity and mortality of COVID-19 were assessed.<br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 20 publications
1
31
0
3
Order By: Relevance
“…The observed finding can also be explained because of the increasing age and age‐related morbidity, which were implicated as important attributes for increased case fatality of 18.7% for patients between 60 and 69 years of age and of 35.8% for patients of 70 and 79 years of age 47 . The mortality was lower than reported among cirrhotic liver disease patients with COVID‐19, for whom outlined mortality was 26%‐40%; this strongly correlated with a higher Child‐Pugh class and a higher MELD score 8,36,48‐51 …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The observed finding can also be explained because of the increasing age and age‐related morbidity, which were implicated as important attributes for increased case fatality of 18.7% for patients between 60 and 69 years of age and of 35.8% for patients of 70 and 79 years of age 47 . The mortality was lower than reported among cirrhotic liver disease patients with COVID‐19, for whom outlined mortality was 26%‐40%; this strongly correlated with a higher Child‐Pugh class and a higher MELD score 8,36,48‐51 …”
Section: Discussionmentioning
confidence: 90%
“…47 The mortality was lower than reported among cirrhotic liver disease patients with COVID-19, for whom outlined mortality was 26%-40%; this strongly correlated with a higher Child-Pugh class and a higher MELD score. 8,36,[48][49][50][51] The current meta-analysis included twelve studies with a relatively high number of hospitalized liver transplant patients with COVID-19 from diverse geographical regions. The most commonly outlined symptoms among the hospitalized liver transplant cohort with COVID-19 were fever (71%), cough (62%), dyspnea (48%), and gastrointestinal symptoms (28%).…”
Section: Discussionmentioning
confidence: 99%
“…These comorbidities play a vital role in segregating AI models that can be independently trained for effective diagnosis and COVID-19 severity prediction. The selected comorbidity studies [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ] were taken from https://pubmed.ncbi.nlm.nih.gov/ . Figure 5 shows the number of subjects with comorbidities enrolled in the ARDS-based studies.…”
Section: Comorbidity and Ardsmentioning
confidence: 99%
“…Bajaj et al ( 40 ) also indicated that cirrhosis COVID-19 patients needed a higher BiPAP/ventilation. A multicenter study from South Korea demonstrated that the incidence of ARDS was higher in cirrhosis COVID-19 patients ( 41 ). Therefore, a close monitoring of coagulation function and diagnostic imaging for VTE should be early implemented in COVID-19 patients with preexisting cirrhosis.…”
Section: Sars-cov-2 Infection In Cirrhosismentioning
confidence: 99%